Wild races : Scripturalizing empire in British India - Lalruatkima (Lanham, Maryland: Lexington Books/Fortress Academic, 2024)
"This book explores the narrative networks that underlie the empirical dimensions of the worlds we imagine and inhabit. Scripturalizing the empire locates this exploration within an ascendant social formation in the nineteenth century-British India"--
Introduction -- Textures and Tensions of Imperial Imaginations -- Civilizing the Wild Races -- Framing Wildness -- Translations and Translingual Exchanges -- Conclusion.
Includes bibliographical references and index.
Keywords: Ethnology -- India; Sociology; India -- Social life and customs -- 19th century; India -- Politics and government -- 19th century